Inclusive Education, Motor Disorders and School Performance: a bibliographic review study (Research, Society and Development, 2020)
Inclusive Education, based on the concepts of access, permanence, and education of qualities for all, provides opportunities for harmonious development in various spheres of the students' learning process. And school performance is part of this progress, necessary for its performance within the educational environment, regardless of cognitive, social or motor difficulties, such as Coordination Development Disorder (DCD), a phenomenon that can interfere negatively in activities of daily living and students' school performance. The purpose of this literature review is to present studies that guide the DCD. We identified a relationship with school skills in reading, writing and arithmetic from the perspective of Inclusive Education, which can place these children in conditions of exclusion or self-exclusion in front of their peers. Therefore, we consider the need to rethink the school environment, to enable inclusive education for all students who have some specificity. Therefore, we denote the essentiality of studies and discussion for a better understanding of this topic.